Annotated list of ichthyofauna of inland and coastal waters of Sakhalin island. 4. Families Triglidae-Agonidae - Dyldin, Yury V. (Journal of ichthyology)
The fourth part of the report represents the next part of the annotated list of fish species found in the marine (within a 200-mile zone), brackish, and fresh waters of Sakhalin: 113 species from one order, three suborders, 9 families, and 53 genera.